Bullying and oral health in Egyptian adolescents: the moderating role of sense of coherence and resistance to peer influence - Amira H. Elwan; Abdelwahab Samaha; Wafaa E. Abdelaziz (BMC, 2024)
Abstract Background Bullying is the intentional, repeated and prolonged aggressive behavior towards victim(s) who feel powerless to defend themselves. It could influence adolescents' mental health. Some adolescents possess coping skills which enable them to overcome such adversities. The present study assessed the association between bullying, sense of coherence (SOC), resistance to peer influence (RPI) and oral health in Egyptian adolescents. Materials and methods A cross-sectional survey that included 12-16 year old adolescents attending 6 schools in Damanhour, Egypt was conducted from March to December 2023. Data were collected through clinical examination and self-administered questionnaires. Clinical examination assessed dental caries (DMFT), oral hygiene (plaque index) and gingival condition (gingival index). Toothbrushing frequency and sugar consumption were assessed by (World Health Organization-child form), bullying (Revised Olweus Bully Victim Questionnaire), SOC (Sense of Coherence Scale-Short Form) and RPI (Resistance to Peer Influence Questionnaire). The independent variables were bullying, SOC and RPI. The dependent variables were untreated caries, gingival inflammation and toothbrushing frequency. Multivariable multilevel regression assessed the relationship between the independent and dependent variables after adjusting for potential confounders. Adjusted regression coefficients (B), adjusted odds ratios (AOR) and 95% confidence intervals (CI) were calculated. Effect modifications by SOC and RPI were evaluated. Results The response rate was 95.25% (N = 602), mean (SD) age was 14.01 (1.15). Half of the students (49.83%) were girls. About 42% had untreated caries, only 15.78% brushed their teeth twice daily and the mean (SD) gingival index was 1.57 (0.40). About 25% were victims, (9.30%) bullies and (18.60%) bully-victims. Victims showed significantly lower odds of twice daily toothbrushing (AOR = 0.52, p = 0.04). Bullies and bully-victims showed non-significantly higher odds of untreated caries (AOR = 1.42, p = 0.25), (AOR = 1.21, p = 0.42), respectively. Bullying was not associated with gingival inflammation. Higher SOC and RPI mitigated the impact of bullying on untreated caries and toothbrushing frequency. Conclusion Bullying was associated with higher odds of untreated caries and lower odds of twice daily toothbrushing in Egyptian adolescents. Higher SOC and RPI alleviated this relationship, highlighting the importance of individual coping strategies to oral health.